How Acne Bumps Cause the Blues: The Influence of Acne Vulgaris on Self-Esteem - S.M. Gallitano, MD; D.S. Berson, MD (Wolters Kluwer, 2018)
Acne vulgaris is one of the most common dermatologic complaints. Although dermatologists are skilled at treating acne, invisible psychological scars can be left by the disease. We review 13 articles that examined the effect of acne vulgaris on patients' self-esteem. Overall, these studies demonstrated that acne has a negative effect on self-esteem among patients of all age groups. These effects most strongly affect women and those with severe acne (both subjectively and objectively). Despite the impact on self-esteem, only a minority of patients seek medical treatment, and even fewer seek treatment from a dermatologist. As dermatologists, we are trained in managing acne. We can provide early and effective treatment that improves both the physical and psychological effects. It is up to us to bridge the gap between those suffering from acne and their access to medical treatment. Keywords: acne vulgaris, self-esteem, acne, isotretinoin, quality of life